Educational Curriculum to Improve Clinical Outcomes in Diabetes Mellitus Patients: A Systematic Review - Anita Kumala Hati; Nanang Munif Yasin; Susi Ari Kristina; Lutfan Lazuardi (Indonesian Journal of Pharmacy, 2023)
The success of controlling the current condition of Diabetes Mellitus (DM) is not only determined by the help of medicine. DM therapy management is strongly supported by the success of providing education to DM patients, so that patients comply with treatment, adopt a healthy lifestyle, and can prevent complications that can end in death. This systematic review aims to find out what curriculum or content of educational materials needs to be given to DM patients to improve the achievement of clinical outcomes. Sage, Scient direct, and Pubmed were searched for relevant articles published between 2012 and 2022 using multiple search terms. STROBE tools were used to conduct quality assessments. Following that, a narrative synthesis of the findings was performed yield 1619 citations. After de-duplicating and screening, 18 studies were eligible for inclusion giving results. Educational materials related to diet/nutrition (n=17), physical activity (n=15), DM treatment (n=14), complications and risk factors (n= 13), goal setting or Healthy Living with DM (n=13), monitoring blood glucose levels parameters (n=11), description of DM (n=7), mental health (n=5), and foot care DM (n= 4). The review was hampered by the poor quality of the included studies. However, the evidence presented shows that educational materials provided to DM patients can improve clinical outcomes. Overall, the evidence base for educating DM patients in the community is still limited, and further research is needed.